Test to failure of a steel truss bridge – Calibration of assessment methods - Blanksvärd, Thomas; Häggström, Jens; Nilimaa, Jonny; Sabourova, Natalia; Grip, Niklas; Täljsten, Björn; Elfgren, Lennart; Carolin, Anders; Paulsson, Björn; Tu, Yongming (Luleå tekniska universitet, Byggkonstruktion och -produktion, 2014)
The steel truss railway bridge at Åby River was built in 1957 with a span of 32 m (105 feet). In 2012 it was replaced by a new steel beam bridge and the old bridge was placed beside the river. It was tested to failure to study its remaining load-carrying capacity in September 2013. The test was carried out by Luleå University of Technology by commission from Trafikverket as a part of the European Research Project MAINLINE (www.mainline-project.eu). In this paper some preliminary results are given. Two hydraulic jacks, anchored by cables to the bedrock, pulled the bridge downwards. The bridge remained elastic up to about three times the original design load and the load could then be almost doubled with substantial yielding deformations before a buckling failure appeared in the top girders for a load of ca. 11 MN (1000 short tons) for a midpoint deflection of ca. 0, 2 m (8 inches). No brittle or fatigue failure in any of the joints appeared and the bridge proved to behave in a ductile way with a substantial hidden capacity. Godkänd; 2014; 20140820 (jonnil); ISBN for host publication: 9780429227165, 978-1-138-00103-9, 978-1-315-76069-8 Centrum för riskanalys och riskhantering, CRR, Sveriges Bygguniversitet, Mainline-MAINtenance, renewaL and Improvement of rail transport iNfrastructure to reduce Economic and environmental impacts